Compliance With Protective Behavioral Recommendations in the Outbreak of COVID-19 Among People Working in the Urban-Based Informal Economy in Southern Ethiopia - Zewude, Bewunetu; Melese, Belayneh; Habtegiorgis, Tewodros; Tadele, Mihret; Solomon, Weynishet (Frontiers in Public Health, 2021)
Regardless of the advocacies made by the media and numerous organizations about the need for preventing the spread of COVID-19, there still exists a gap as far as compliance to regular implementation of the preventive mechanisms within communities is concerned. The purpose of the present study was, therefore, to examine compliance to personal protective behavioral recommendations to contain the spread of COVID-19 among urban residents engaged in the informal economic activities in Wolaita Sodo town, Southern Ethiopia. A cross-sectional study design was used where quantitative data were collected through the survey research method. Three hundred and eighty-four participants of the urban-based informal economy were randomly selected and contacted in their own natural settings with an interviewer-administered questionnaire. Data were inserted into SPSS software for analysis that involved both descriptive and inferential statistics, including frequency and percentage distributions, binomial and multinomial logistic regressions. The results of the research indicated that only 35.4% of the respondents regularly wore a mask. In addition, 54.9% of the survey participants disclosed that they do not clean their hands with disinfectants after touching objects under circumstances where they cannot get access to water and soap. Moreover, the most commonly reported reason of respondents for non-compliance to regular wearing of a mask has been its inconvenience or discomfort (62.8%), followed by the need to appear indifferent because most people around them do not wear a mask (25.2%). Furthermore, experiences of the respondents of regularly wearing a mask are significantly associated with regular attendance of the media regarding the preventive mechanisms of COVID-19 (OR = 0.224; P < 0.001; 95%C.I: 0.109–0.460), knowledge of someone ever infected by COVID-19 (OR = 0.402; P < 0.05; 95%C.I: 0.190–0.851), the belief that COVID-19 causes a severe illness (OR = 0.444; P < 0.05; 95%C.I: 0.201–0.980), and perception of the likelihood of dying as a result of infection by COVID-19 (OR = 0.374; P < 0.01; 95% C.I: 0.197–0.711). The authors have found a low level of compliance to the recommended safety measures, especially wearing of masks. It is, therefore, important that continued efforts of raising awareness should be done by all the concerned bodies. Above all, urban safety net programs that aim at keeping such social groups at home, at least during the critical wave of the pandemic, should also be strengthened.